Silver Nanoparticles in Dental Biomaterials - Corrêa, Juliana Mattos; Mori, Matsuyoshi; Sanches, Heloísa Lajas; Cruz, Adriana Dibo da; Poiate, Edgard; Poiate, Isis Andréa Venturini Pola (International Journal of Biomaterials, 2015)
Silver has been used in medicine for centuries because of its antimicrobial properties. More recently, silver nanoparticles have been synthesized and incorporated into several biomaterials, since their small size provides great antimicrobial effect, at low filler level. Hence, these nanoparticles have been applied in dentistry, in order to prevent or reduce biofilm formation over dental materials surfaces. This review aims to discuss the current progress in this field, highlighting aspects regarding silver nanoparticles incorporation, such as antimicrobial potential, mechanical properties, cytotoxicity, and long-term effectiveness. We also emphasize the need for more studies to determine the optimal concentration of silver nanoparticle and its release over time.